jet lag - Rappenecker, Gert; Galerie Martina Detterer, Frankfurt am Main (Frankfurt : Galerie Martina Detterer, 1994)
Armstrong, L.C. ; French, Christopher ; Hopkins, Peter ; Meister, Ulrich ; Miller, John ; Mitchell, Curtis ; Muniz, Vik ; Rosenberg, Aura ; Stövhase, Susanne ; Tomaselli, Fred ; Van Bossche, Guy ; Van Lamsweerde, Inez ; Wallinger, Mark ; Wastijn & Deschuymer ; Biefer/Zgraggen
jet lag, Galerie Martina Detterer, Frankfurt, 29. Januar bis 31. März 1994
boek